2012
DOI: 10.2478/s11536-011-0153-7
|View full text |Cite
|
Sign up to set email alerts
|

B-cell activating factor (BAFF) — a new factor linking immunity to diet?

Abstract: AbstractB cell activation factor (BAFF) is a recently discovered member of the TNF ligand superfamily secreted by adipocytes, previously linked to autoimmune and lymphoproliferative disease. The aim of this study was to investigate the relationship between BAFF plasma levels and the non-modified, usual dietary composition as well as obesity-related anthropometric parameters in a cohort of 58 obese and non-obese Central-European Caucasian individuals. We found that BAFF had an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…It has been reported that plasma BAFF levels are gender-dependent, proportional to BMI, percentage of body fat, and significantly different between obese and non-obese individuals [26]. The obese females presented higher BAFF levels compared with non-obese females or obese males.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that plasma BAFF levels are gender-dependent, proportional to BMI, percentage of body fat, and significantly different between obese and non-obese individuals [26]. The obese females presented higher BAFF levels compared with non-obese females or obese males.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that mature adipocytes produce BAFF, which has been identified as an adipokine with metabolic effects [3][4][5]. The aim of this study was to elucidate the role of BAFF deficiency in metabolic regulation through exploring the molecular mechanism underlying the effect of BAFF depletion on improved glucose tolerance in HFD-fed BAFF -/-mice.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that treatment with recombinant BAFF protein impaired insulin-mediated glucose uptake in 3T3-L1 adipocytes. BAFF plasma levels were significantly correlated with body fat and dietary composition in obese CentralEuropean Caucasian individuals [5], and the levels were also observed to be significantly higher in Japanese patients with nonalcoholic fatty liver disease [6].…”
Section: Introductionmentioning
confidence: 94%
“…Several studies have reported positive correlations between plasma BAFF level and metabolic diseases, such as insulin resistance and non-alcoholic fatty liver disease [ 3 , 4 , 5 , 6 , 7 ]. We also previously reported a protective effect of BAFF depletion against high-fat diet-induced glucose intolerance using BAFF −/− mice on a high-fat diet, which exhibited improved insulin sensitivity and potentiated adipose tissue function [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although BAFF was originally identified as a secretory protein in immunocytes, recent studies have described that mature adipocytes also produce BAFF and its receptors, suggesting a role of BAFF in the regulation of energy metabolism [ 2 ]. It has recently been reported that a circulating BAFF level is positively correlated with body mass index in individuals with obesity [ 3 ], and patients with non-alcoholic fatty liver disease have increased levels of serum BAFF [ 4 ]. Several studies using mouse models also have shown a positive correlation between BAFF and energy metabolism dysregulation.…”
Section: Introductionmentioning
confidence: 99%